Reductions in World Health Organization risk drinking levels as a primary efficacy end point for alcohol clinical trials: a review - Witkiewitz, Katie; Anton, Raymond F.; O’Malley, Stephanie S.; Hasin, Deborah S.; Silverman, Bernard L.; Aldridge, Arnie; Mann, Karl (JAMA psychiatry, 2025)
Alcohol use disorder (AUD) is a highly prevalent and costly psychiatric disorder. Abstinence has been considered the optimal outcome of treatment for AUD. Yet, most individuals with AUD do not seek treatment because they do not have a goal of abstinence. The Food and Drug Administration (FDA) has recently qualified reductions in drinking, defined by at least a 2-level reduction in the World Health Organization risk drinking levels (WHO RDLs), as a primary end point for alcohol pharmacotherapy trials. The approval of drinking reductions as an end point for alcohol clinical trials aligns with an accumulating literature on drinking reductions in the alcohol field. This article provides a narrative review of 34 articles that have examined WHO RDLs as a surrogate marker of how people with AUD feel and function.Results from epidemiological studies, community samples, and clinical trials indicate that drinking reductions are associated with improvements in how patients feel and function, including reduced risk of substance use disorder and medical and psychiatric diseases and reductions in alcohol-related consequences, craving, and health care costs. Drinking reductions are also associated with improvements in functioning and quality of life. Drinking reductions are also achieved by most clinical trial participants, and effect sizes for the WHO RDL reductions for active medications vs placebo are similar to or better than alternative end points.The FDA acceptance of reduction in WHO RDLs as a primary end point for alcohol clinical trials may increase opportunities for AUD medications development, encourage patients to seek treatments that target drinking reductions, and engage clinicians in prescribing medications shown to be effective in supporting drinking reductions. The WHO RDLs may be particularly useful for targeted drinking reductions in clinical practice. Qualification of the WHO RDL end point facilitates a paradigm shift toward a harm reduction approach in AUD treatment.